Significant Liquid-Structure Theory of Viscosity and Self-Diffusion of the Alkali Metals - Hsu, Chen C. (1972)
Significant liquid-structure theory has been used to calculate the transport properties of the alkali metals. Unlike previous calculations, the volume and temperature dependence of the solid-like structure has been taken into consideration. Equations for the potential energy as a function of volume of the alkali metals, which lead to agreement between calculated and experimental values of thermodynamic and transport properties, are given. The calculated results are in satisfactory agreement with the experimental data.